Administrative career : a work opportunity for optometrist in the public sector - Rubio Rincón, Gina Sorel (Universidad de La Salle. Revistas. Ciencia y Tecnología para la Salud Visual y Ocular., 2006)
In Colombia, optometrists may work in the public sector. Law 9009 of 2004 states «norms to regulate the public employment, the administrative career, the public management and other dispositions»; and it is implemented in order to have access to the citizen administration with a better personal and professional quality, satisfying then the general interests, the human resources professionalism, the responsibility of the public employee, and an increase in the efficacy levels, in the public function. Public employment, which is part of the public function, must be subjected to selection processes under the principles of merit, free concurrence, and equality in the entry, publicity, transparency, and specialization of the technical entities in charge of the selection processes, guaranty of impartiality in the entities in charge of the processes, reliability and validity of the selection mechanisms. The administrative career, as a technical system of personnel administration, wants to guarantee the efficiency in the public administration, and the stability and equality in opportunities for the access and promotion in the public position. Therefore it gives more opportunities for the health professionals, especially for optometrists.